An Updated List of Gandhara Palettes and Their Utility for the Study of Hybridity - Christos Nikolaou (Journal of Open Humanities Data, 2023)
The Gandhara palettes have been studied in the field of Gandharan art, particularly for their connection to the broader school and its cultural trajectories. A complete repository of the palettes is useful for the study of the artefacts and their relation to Gandharan art. The database seeks to produce a new depository for the palettes as well as more ambiguous artefacts which may have fulfilled similar roles. The dataset described in this paper provides other information such as bibliography, material and estimated chronology which allows for statistical analysis or unpacking correlations of types and chronologies.